2003
DOI: 10.17221/4104-pse
|View full text |Cite
|
Sign up to set email alerts
|

Fast prediction of quality parameters in whole seeds of oilseed rape (Brassica napus L.)

Abstract: A calibration equation for NIRSystems 6500 instrument was derived at VSTE Jevíèko using the measurement of broad collection of Czech samples of winter rape, allowing sufficiently accurate prediction of content of dry matter (DM), crude protein (XP), crude fat (XL), glucosinolates (GSL), oleic and linoleic acids in an extremely short time. The prediction accuracy was verified on a validation file (n = 60). The coefficients of determinance (R 2 ) were 0.83 for XP, 0.71 for XL, and 0.84 for GSL. The prediction ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 3 publications
1
13
2
1
Order By: Relevance
“…These results confirm the conclusions drawn by WILLIAMS and SOBERING (1992), , VELASCO et al (1999a) that NIRS analysis may facilitate effective selection of oilseed rape genotypes with the desired content of FA in oil similar to other significant parameters of quality (MÍKA et al 2003). NIRS method enables the analysis of intact rape seeds in an extremely short time without loss of their germination capacity.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results confirm the conclusions drawn by WILLIAMS and SOBERING (1992), , VELASCO et al (1999a) that NIRS analysis may facilitate effective selection of oilseed rape genotypes with the desired content of FA in oil similar to other significant parameters of quality (MÍKA et al 2003). NIRS method enables the analysis of intact rape seeds in an extremely short time without loss of their germination capacity.…”
Section: Resultssupporting
confidence: 89%
“…A number of authors ( VAN DE VOORT et al 1992;WILLIAMS & SOBERING 1992;SATO 2002;MÍKA et al 2003) confirmed the suitability of NIRS (Near Infrared Reflectance Spectroscopy) as a non-destructive, rapid, cheap and relatively accurate method for determining the seed quality (content of glucosinolates, oil, proteins, dry matter and fatty acids) of oilseed crops. In all measured components including FA high significance of the correlation between NIRS and the reference method (GC) was found (VELASCO et al , 1999a.…”
mentioning
confidence: 99%
“…The FA compositions in seeds were determined by near-infrared reflectance spectroscopy (NIRS; Foss NIRSystems Inc., USA) using standard methods with three replicates (Mika et al, 2003). Seed oil content and protein content was determined by using nuclear magnetic resonance (NMR) (mq-20, Bruker, Germany) with at least five biological replicates according to Burns et al (2003) with modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Ten main agronomic traits were measured in mature plants, including plant height, primary branch number, length of main inflorescence, number of siliques on the main inflorescence, number of siliques per plant, length per silique, number of seeds per silique, 1,000-seed weight, seed yield per plant, and seed oil content. Seed oil content was determined by near infrared spectroscopy (NIRS) using standard methods (Mika et al 2003).…”
Section: Measurement Of Agronomic Traitsmentioning
confidence: 99%